The Cash Transfer and Intimate Partner Violence Research Collaborative contributes to strategies of global development organizations - CGIAR Research Program on Policies, Institutions, and Markets (2019)
In 2018, PIM research about the link between cash transfer programs and intimate partner violence led to the launch of the "Cash Transfer and Intimate Partner Violence Research Collaborative”. In 2019, this partnership advanced an ambitious research agenda and informed strategies of the World Health Organization and of United Kingdom’s Department for International Development.